Association of ADIPOQ single nucleotide polymorphisms with the risk of intracranial atherosclerosis. (4th May 2017) - Cui, Min; Zhou, Shiming; Li, Rui; Yin, Zegang; Yu, Mingming; Zhou, Huadong
Abstract : Background : The genetic mechanism of the racial distribution difference of intracranial atherosclerosis (ICAS) is unclear. The single nucleotide polymorphisms (SNPs) may be associated with different genetic susceptibility to ICAS. At present, the correlation between ADIPOQ gene SNPs and the risk of ICAS remains unknown. Methods : Continuous inpatients were selected and divided into ICAS group and control group. Computed tomography angiography was performed to observe intracranial arteries. ADIPOQ SNPs were detected using the ligase detection reaction-PCR. The correlation between the identified SNPs and ICAS was determined using the binary logistic regression analysis. Results : This study contained 602 patients in total, including 199 ICAS and 403 control cases. The binary logistic regression analysis showed that the AG/AA genotype of the rs2241767 (OR = 2.242, 95% CI: 1.037–4.878, P = 0.040) and the AG/GG genotype of the rs182052 (OR = 1.822, 95% CI: 1.111–2.987, P = 0.017) were closely related to the risk of ICAS after adjusting for conventional cardiovascular risk factors. The haploid analysis results indicated that the incidence of the A-G haplotype of the rs2241767 and rs182052 was higher in the ICAS group than in the control group ( P = 0.026). Conclusions : The SNPs of the ADIPOQ gene are closely related to increased risk of ICAS in Chinese Han population.